GITELMAN SYNDROME PRESENTING AS HYPOKALEMIC PERIODIC PARALYSIS - Dr. Vijaykumar Gulve; Dr. Vishal Balaso Shewale; Dr. Harsh Choudhari; Dr. Bhushan Labhade; Dr. Kranthi Koleti; Dr. Parth Maindarkar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Gitelman syndrome (GS) is a very rare inherited disorder characterized by renal tubular dysfunction, primarily affecting the kidneys’ ability to reabsorb electrolytes. There is a mutation in the gene SLC12A3 in the distal convoluted tubule of the nephron that causes this disease. Symptoms include weakness, fatigue, tingling, and muscle spasms. Diagnosis is often incidental during lab tests or when symptoms appear. Treatment focuses on correcting electrolyte imbalances with magnesium and potassium supplements, aldosterone antagonists like spironolactone, and NSAIDs for symptom management. In the presented case, a 26-year-old female was diagnosed with Gitelman syndrome after presenting with tingling and spasms. The treatment included spironolactone, vitamin D3, febuxostat, indomethacin, and a potassium supplement. Regular follow-up is essential to prevent further complications.